Integration of Local Wisdom and Digital Innovation: A Strategic Management Model for Islamic Higher Education Institutions in Developing Countries - Nento, Shinta; Abdullah, Abdul Haris (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
Islamic Higher Education Institutions (IHEIs) in developing countries face a dual challenge of maintaining cultural identity while pursuing digital transformation. Although digital innovation has been widely studied as a driver of efficiency and competitiveness, limited empirical research explores how local wisdom functions as a strategic enabler in higher education management. This study addresses this gap by proposing a hybrid strategic management model that integrates local wisdom, digital innovation, and strategic leadership. Using a comparative case study of Indonesia, Malaysia, and Egypt, data were collected from secondary sources, including policy documents, institutional reports, and peer-reviewed literature, and analysed through thematic content analysis with cross-case coding. Findings reveal that local wisdom provides legitimacy and cultural grounding, while digital innovation strengthens adaptability and efficiency; strategic leadership integrates both dimensions into sustainable institutional transformation. Theoretically, this study contributes to value-based strategic management literature by challenging the modernity–tradition dichotomy in non-Western contexts. Practically, it offers actionable insights for policymakers and administrators to design strategies that balance technological adoption with the preservation of institutional identity.